How cities grow smart? - Guerreiro, Maria Rosália; Lopes, Bárbara (II International Conference on 'URBAN e-PLANNING', 2017)
The idea of smart cities emphasises the deeper understanding of how urban systems function in a sustainable way. The aim of this study was to investigate how cities grow naturally according to its function. Is there any spatial pattern we can recognise as a model for growing more sustainable cities? An axial model of the city of Lisbon (Lisboa) was constructed according to Space Syntax theory and methodology which is a way for researching cities as self-organising systems in order to understand how social and economic processes shape space over time. It was found that a specific pattern of street network emerges from the model using different topological or syntactic measures, like integration and choice, which evaluates the accessibility and potential movement of the street network. This pattern called “deformed wheel” in Space Syntax literature is the one which guarantee the better function of the city because it makes the most uniform and economic distribution of the flows through the urban system. The understanding of this pattern street network is crucial for the sustainability of the urban planning and design of the city of Lisbon. Although the pattern of deformed wheel is disrupted at certain points of the web, especially in the areas of recent development, there exists the possibility to make the city growth smart if we improve certain public spaces (hubs of the network) which reinforce mutually the global and local accessibility in the city.